2020
DOI: 10.1177/2042018820943377
|View full text |Cite
|
Sign up to set email alerts
|

Malignancy risk in adults with growth hormone deficiency undergoing long-term treatment with biosimilar somatropin (Omnitrope®): data from the PATRO Adults study

Abstract: Background: To assess the safety (particularly the occurrence of malignancies) of growth hormone (GH) replacement (Omnitrope®) in adults with GH deficiency, using data from the ongoing PATRO Adults post-marketing surveillance study. Methods: PATRO Adults is being conducted in hospitals and specialized endocrinology clinics across Europe. All enrolled patients who receive ⩾1 dose of Omnitrope® are included in the safety population. Malignancies are listed as adverse events under the MedDRA System Organ Class ‘n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 22 publications
(44 reference statements)
0
5
0
Order By: Relevance
“…The current analysis also includes 69 reports of malignancy events (in 60 patients). The occurrence of on-study malignancies in PATRO Adults has been reported previously (based on data from July 2018) [ 14 ]. While the data did not in general support a carcinogenic effect of rhGH in adults with GHD, an increased risk of second new malignancies in patients with previous cancer could not be excluded.…”
Section: Discussionmentioning
confidence: 85%
“…The current analysis also includes 69 reports of malignancy events (in 60 patients). The occurrence of on-study malignancies in PATRO Adults has been reported previously (based on data from July 2018) [ 14 ]. While the data did not in general support a carcinogenic effect of rhGH in adults with GHD, an increased risk of second new malignancies in patients with previous cancer could not be excluded.…”
Section: Discussionmentioning
confidence: 85%
“…Therefore, the safety of biosimilar growth hormone products was carefully followed not only by routine pharmacovigilance but also by individual centers, networks of investigators, and registers, especially PATRO. The safety and efficacy profile turned out to be similar to the originator product [ 30 33 ].…”
Section: Resultsmentioning
confidence: 98%
“…No increased risk was seen for neoplasia compared with other GH treatments [ 124 ]. Further analysis from the same database including 1293 adults, of which 637 (49.3%) were GH treatment-naïve at study entry and the majority having multiple pituitary hormone deficiency ( n = 1128, 87.2%), demonstrated that GH treatment did not result in an increased cancer risk, although an increased risk of second new malignancies in patients with previous cancer could not be excluded [ 125 ]. Conversely, the SAGhE studies of GH therapy in young adults with childhood-onset GHD suggested an increased risk for certain cancer types or a trend towards increased risk of mortality with GH therapy [ 17 , 126 ].…”
Section: Gh Treatment In Cancer Survivors During Adulthoodmentioning
confidence: 99%